Legal Aspects of Seller's Liability in a Sales and Purchase Agreement with an Installment Payment System - Winta Hayati; Taufika Hidayati (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
System Installment payment system in a sale and purchase agreement has become a common practice in modern trade transactions that require a clear legal basis for the payment of installments. modern trade transactions that require a clear legal basis to protect the rights of the parties. protect the rights of the parties. This research aims to examine the legal aspects of legal aspects of seller liability in a sale and purchase agreement with an installment payment system. installment payment system. This study elaborates on the details of civil law in installment payments, investigates the legal implications for consumers. installment payments, investigates the legal implications for consumers and sellers, and analyzes how the seller's liability can be enforced in the framework of the applicable civil law in Indonesia, particularly when there are default or dispute between the parties. The research uses the method of normative juridical method with a statutory approach and conceptual approach, analyzing various primary and secondary legal sources related to installment payment system. The results of the research show that the seller's liability in the installment payment system has a complex legal basis based on the Civil Code, especially Article 1. complex legal basis based on the Civil Code, especially Articles 1320 and 1338 which emphasize the validity of the agreement. 1338 which emphasize the validity of the agreement and the principle of good faith. LAW Consumer Protection Law strengthens this aspect of seller liability by emphasizing consumers' rights to transparent information and product quality assurance. product quality. In the event of default, the seller may be subject to sanctions in the form of compensation which includes costs, losses, and interest.